Pluripotent Stem Cells as an In Vitro Model of Neuronal Differentiation - Kerkis, Irina; Hayashi, Mirian A. F.; Lizier, Nelson F.; Cassola, Antonio C.; Pereira, Lygia V.; Kerkis, Alexandre (IntechOpen, 2011)
None